Public sector procurement: the effectiveness of monitoring mechanism / Aida Maria Ismail ...[et al.] - Ismail, Aida Maria; Hasan, Mohammad Rizal; Clark, Colin; Mohamed Sadique, Raziah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
Issues in public sector procurement have been increasing lately. These issues either related to non-compliance or frauds have been highlighted each year by Auditor General. However, there are seems that no effective solutions in overcoming these issues. Therefore, this study attempts to examine the relationship between monitoring mechanisms and procurement issues in public sectors. The monitoring mechanisms that were focus are on the effectiveness of procurement procedure and the role of internal auditors towards issues in public procurement. The finding of the research has found that no job rotation in the high-risk area is the top factor that influences public procurement issues. Normally, without job rotations, it will create opportunities for procurement officers to collude with outsiders to commit fraud. Besides job rotation, the other factors that influence procurement issues are related with components of control activities in the COSO framework. The major finding of the study has shown that both procurement procedure and role of internal auditor do have negative relationship towards procurement issues in public sector. However, only procurement procedure has significant relationship towards procurement issues in public sector compared to the role of internal auditors. In conclusion, both monitoring mechanism use in this study in terms of procurement procedure and role of internal auditors have affect procurement issues in public sector.